ACOMPETITIVENESS INDEX AND STRATEGIC ANALYSIS OF MICRO, SMALL AND MEDIUM ENTERPRISES IN FACE OF ASEAN ECONOMIC COMMUNITY (AEC) - Adini Nur Azizah (EKPI 16 UMY 159, 2016)
The implementation of ASEAN Economic Community (AEC) in 2015, brings our attention to the Micro, Small and Medium Enterprises (MSMEs) as the important players in Indonesian economy. To prepare for it, the government has made various efforts for the community, so that they can carry out business development and compete in the AEC. But apparently lack of government's efforts in providing support to MSMEs will result in mal-distribution of MSME growth. It increases lagging impact on the local MSMEs in competing with foreign enterprises. It is also responsible for the deterioration of the majority of MSMEs communities in Indonesia, such as the ones in Yogyakarta province. The low competitiveness of Yogyakarta MSMEs will result in the inability to compete with foreign enterprises. Lack of strategy to deal with AEC in 2015 will result in declining opportunity for Yogyakarta MSMEs to compete with foreign enterprises. This study aims to analyze the competitiveness index of Yogyakarta MSMEs and also to analyze the condition of Yogyakarta MSMEs, both externally and internally. The method used to calculate the competitiveness index is the theory of element diamond porter and the Likert scale. Another analysis tool used is the SWOT (Strength, Weakness, Opportunity and Threat) method. By using SWOT analysis method, the expected outcome is that researcher can offer strategies to the Yogyakarta MSMEs in order to compete in AEC. In addition, the result strategy can be used as a reference for policy-makers and authorities to strengthen the competitiveness of Indonesian MSMEs, especially Yogyakarta MSMEs, in facing the ASEAN Economic Community (AEC) 2015. Keywords: UMKM, Competitiveness Index, ASEAN Economic Community (AEC)